Shamans, nostalgias, and the IMF: South Korean popular religion in motion - Kendall, Laurel (Univ. of Hawaii Press, 2009)
Introduction -- Shifting intellectual terrain : superstition becomes culture and religion -- Memory horizons : kut from two ethnographic presents -- Initiating performance : Chini's story -- The ambiguities of becoming : phony shamans and what are mudang after all? -- Korean shamans and the spirits of capitalism -- Of hungry ghosts and other matters of consumption -- Built landscapes and mobile gods -- Conclusion